Analysis of Basalt and Thermoplastic Hybrid Composites (Journal of Fiber Bioengineering and Informatics, 2018)
This study focusses on investigations based experiments which are carried out to check the mechanical& thermal properties of woven epoxy composite laminates from Basalt/PP, Basalt/PET fibers andvice versa. Fabricated composite samples are subjected to mechanical and thermal characterization.The results reveal that, there is noticeable improvement in mechanical properties with the changeof weaves in basalt hybridized composites. Interfacial linkages/bond between fibers and resin causea significant modulus increase in composites. Thermal behavior of fiber and composite was observedby Thermal Gravimetric Analysis and Differential Scanning Calorimetric. Thermal properties are alsoaffected by hybridization. Thermal conductivity is strongly affected by resin properties. A demonstrationof ruptured surface was done by Fractography. The results show that hybridized basalt in differentcomposites leads to a significant improvement in the dynamic and static mechanical properties ofcomposites. Fiber type, weave structure, and resin properties greatly affect the mechanical properties ofcomposites made with hybrid basalt fabrics.